A STUDY ON LABOUR COMPETENCE: THE ROLE OF DEMONSTRATION IN SME MANUFACTURING UNITS. - GANESH, P. (The journal of contemporary issues in business and government, 2022)
The main contribution is thus to inspect the effects of LP on both dimensions, i.e. productivity and distribution, whereas most of the studies of related nonfiction are restricted to one of those aspects. All approximations are achieved for a large illustration of manufacturing and service Industry with more than five hundred employees and a restricted sample including only unionized firms. This study evaluated the effect of performance managing practices on employee productivity at the State department of Labour. The performance management practices were comprised of employee's appraisal as well as provision of feedback on employee's performance. The study undertook a descriptive research design, where primary data was collected through structured questionnaires on the targeted population of middle and lower level employees. Respondents was identified and random stratified sampling was undertaken to come up with a sample size of 68 respondents. Questionnaires were answered and returned, which comprised of 67.6% response rate. The study found that there was a strong positive correlation of both employee appraisal and employees performance feedback on employee productivity. The study therefore recommended that organizations to undertake both appraisal for their employees as well as offer feedback on their performance as it increased the productivity of the employees.